Gama rays mediated improvement of catalytic efficiency and thermostability of glucoamylase by replacing active site leucine to isoleucene from super koji (Aspergillus oryzae) - Anam Saqib; Saif -ur-Rehman; Hazrat Ali; Noor Hassan; Asad Ali; Muhammad Hamid Rashid (PLoS ONE, 2025)
Glucoamylase is considered as an essential enzyme in food industry. However, lowere catalytic efficiency and weak thermostability confine its application in food industry. Therefore, the current study was aimed to improve catalytic efficiency and thermostability of glucoamylase by replacing active site leucine to isoleucene from Super Koji (Aspergillus oryzae) using gama rays mediated point mutation. High catalytic efficiency and thermostability of glucoamylase from mutant Aspergillus oryzae M-60(5) (screened from 51 mutants) was achieved due to a point mutation, i.e., Leu203 → lle in active site. The SDS-PAGE molecular mass of parent and mutant glucoamylase was 63.1 kDa, while mutant glucoamylase showed; productivity =  9.7 U ml‒1, kinetic constants kcat = 118 (1.62 fold), (kcat/Km) = 1899 (4.75 fold) and half-life at 55 °C for 45 min (1.92 fold). Thermodynamics parameters for starch hydrolysis of parent glucoamylase were; ΔH*= 47.755 kJ mol‒1 and ΔG*= 67.975 kJ mol‒1 while for mutant ΔH*= 44.263kJ mol‒1 and ΔG*= 66.514 kJ mol‒1. The ΔG* of irreversible thermostability for parent and mutant at 55 °C was 104.95 kJ mol‒1 and 101.52 kJ mol‒1respectively. The point mutation altered the conformation of the glucoamylase active site that contributed to improve the functional energy (ΔG*), resulted the stabilization of transition state which made it thermostable and highly efficient in starch hydrolysis.